If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+4x=10(11x-10)
We move all terms to the left:
6+4x-(10(11x-10))=0
We calculate terms in parentheses: -(10(11x-10)), so:We get rid of parentheses
10(11x-10)
We multiply parentheses
110x-100
Back to the equation:
-(110x-100)
4x-110x+100+6=0
We add all the numbers together, and all the variables
-106x+106=0
We move all terms containing x to the left, all other terms to the right
-106x=-106
x=-106/-106
x=1
| 2+0.2x=0.8 | | 5(v-88)=30 | | 360-4x+360-4x=360 | | -10(z+5)=4z-4(2z+7) | | 3(x+40)=21 | | 22=10d-8 | | (x-3)2+8=57 | | 5x+2(3-x)=5x+2(x-3) | | (x-3}2+8=57 | | 360-4x+90-x=180 | | (.4x)+600=x | | 10w=7100w= | | 6x+2(2)=5x+7 | | -47-n=-4(1-11n)+2 | | 4=a-12/3 | | -2(3a+1)=5(1-a) | | 8(1+x)=-22+2x | | X=0.3x5 | | 50=q/10+48 | | 11-x=35 | | 310=58+4x | | 3(x+1)=4(x+6) | | 2(2u-5)=u+2 | | 40+60x=460 | | 2(3x+1)=5(2x+3) | | 11x+14=2x+158 | | 96=4(b+6) | | 26x-125=x | | 7c-2=4c+13 | | 3j-22=-4-3j | | 4(m+4)^2−4m^2+20=276 | | -p+3p=-7+p |